Personality trait differences across types of entrepreneurs: a systematic literature review - Salmony, Florentine U; Kanbach, Dominik K (Review of managerial science, 2022)
The personality traits that define entrepreneurs have been of significant interest to academic research for several decades. However, previous studies have used vastly different definitions of the term "entrepreneur", meaning their subjects have ranged from rural farmers to tech-industry start-up founders. Consequently, most research has investigated disparate sub-types of entrepreneurs, which may not allow for inferences to be made regarding the general entrepreneurial population. Despite this, studies have frequently extrapolated results from narrow sub-types to entrepreneurs in general. This variation in entrepreneur samples reduces the comparability of empirical studies and calls into question the reviews that pool results without systematic differentiation between sub-types. The present study offers a novel account by differentiating between the definitions of "entrepreneur" used in studies on entrepreneurs' personality traits. We conduct a systematic literature review across 95 studies from 1985 to 2020. We uncover three main themes across the previous studies. First, previous research applied a wide range of definitions of the term "entrepreneur". Second, we identify several inconsistent findings across studies, which may at least partially be due to the use of heterogeneous entrepreneur samples. Third, the few studies that distinguished between various types of entrepreneurs revealed differences between them. Our systematic differentiation between entrepreneur sub-types and our research integration offer a novel perspective that has, to date, been widely neglected in academic research. Future research should use clearly defined entrepreneurial samples and conduct more systematic investigations into the differences between entrepreneur sub-types.